Analysis on The Effectiveness of AXIS Mobile Internet Strategy and Identification of Areas for Future Improvements (The Indonesian Journal of Business Administration, 2012)
The market penetration for voice and SMS hasreached 100% and style of communication has change using data(mobile internet). Mobile internet has be new source that isexpected to increase operator revenues. The development ofmobile internet technology from 2G (EDGE) to 3G (HSDPA) andsmart phone supports the development of mobile internet usersin Indonesia. For three years Axis quite successfully apply CostLeadership strategy to compete with the other operators,especially with medium-class operator. In 2011, Axis revenuegrowth target didnâ€™t fit with target which grew only 90% of thetarget of 100%. Axis has a target to 3 major operators inIndonesia within the next two years to reach this target, the Axishave to compete with the current three major operators. Basedon existing problems, AXIS should immediately makeimprovements in all business lines including mobile internet. Thisthesis has focused on analyzing the right strategy for mobileinternet using qualitative data and using Axis Five ForcesFramework and SWOT analysis. The result from Five ForcesFramework is industry of mobile internet have good prospectand using SWOT analysis to find the strength and weakness ofAXIS. From 5 Business level strategies, find the best strategy isdifferentiation strategy.Â Differentiation strategy start fromdevelop customer loyalty program, maintain quality coveragearea of mobile internet, aiming for premium users and bundlingprograms on high-end gadgets are feature or system need toapply in Axis for this strategy.Keywords: mobile internet,Five Forces Framework, SWOT, 5business level strategies